Determining the size of craters on the surfaces of atmosphereless bodies in Solar system with ground-based methods - A. I. Klianchin; V. V. Prokof'eva-Mikchailovskaya (Вісник Астрономічної школи, 2013)
A new method of determining the size of craters on the surfaces of atmosphereless bodies of the Solar system, called spectral-frequency method (SFM), was developed at the Crimean Astrophysical Observatory by V. V. Prokofieva-Mikhaylovska, N. A. Rublevsky in collaboration with V. V. Busarev from SAI (MSU). SFM of studying color- or lightcurves of asteroids allows to obtain information about the size of details on their surfaces with ground-based tools. Visibility of craters is explained with the inverse coherent scattering of solar radiation on the regolith ejected during bodies collisions.